Entropy Numbers of General Diagonal Operators - Kuhn, Thomas (Revista Matemática Complutense, 2005)
We determine the asymptotic behavior of the entropy numbers of diagonal operators D : `p ! `q, (xk) 7! (_kxk), 0 < p, q _ 1, under mild regularity and decay conditions on the generating sequence (_k). Our results extend the known estimates for polynomial and logarithmic diagonals (_k). Moreover, we also consider some exotic intermediate examples like _k = exp(−plog k).